Penyidikan Tindak Pidana Pencabulan Oleh Oknum Guru Terhadap Murid Sekolah Dasar Negeri 08 Kampung Baru Kec. Kupitan Di Unit Perlindungan Perempuan Dan Anak (Ppa) Polres Sijunjung (Studi kasus: LP /B/16/III/2023/SPKT/POLRES SIJUNJUNG) - Fitra Oktoriny; Nuraini Nuraini (Fakultas Hukum Universitas Tamansiswa Padang, 2025)
Investigation is a series of investigator's actions in terms and according to the methods regulated in this Law to search for and collect evidence and with that evidence to shed light on the criminal act that occurred in order to determine the suspect. Law Number 35 of 2014 concerning the protection of women and children is one of the foundations and guidelines for law enforcers when acts of violence, specifically child abuse, occur. The crime of sexual abuse is a form of crime that is handled by investigators or the police, which precisely occurred in the Sijunjung area, the perpetrator was a teacher who had the heart to molest his own students. The formulation of the problem in this research is how to investigate criminal acts of sexual abuse committed by unscrupulous teachers against students at State Elementary School 08 Kampung Baru District. Kupitan at the Sijunjung Police PPA unit in the case study LP/B/16/III/2023/SPKT/Sijunjung Police, what are the obstacles in investigating criminal acts of sexual abuse committed by unscrupulous State Primary School teachers?08 Kampung Baru District. Kupitan at the Sijunjung Police PPA unit in the case study LP/B/16/III/2023/SPKT/Sijunjung Police. What are the efforts to overcome obstacles in investigating criminal acts of sexual abuse that occurred at state elementary school 08 Kampung Baru, Kec, Kupitan, in the PPA unit of Sijunjung Police, case study LP/B/16/III/2023/SPKT/Sijunjung Police. The method used in this research is a sociological juridical approach. The method of processing data in this research is through editing and coding. The results of the research obtained by the author are that the case began with a report from the victim's parents to the Sijunjung Police, followed by investigation, investigation, arrest, search, detention, examination of witnesses, victims and perpetrators and finally making an investigation report ( BAP). Obstacles in carrying out investigations include difficulty in getting witnesses, difficulty in getting information from victims and inadequate supporting facilities. Efforts that can be given are increasing the role of the police in public awareness through counseling or socialization among the community about the importance of the role of witnesses related to criminal acts of sexual abuse against children and it is hoped that there will be cooperation with internal parties such as parents in investigating criminal acts of sexual abuse as well as improving facilities and infrastructure in each area. schools in the Sijunjung area.